2014
DOI: 10.5539/jedp.v4n2p145
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Achievement in and Attitude toward Mathematics of the Finnish Children from Grade 0 to 9—A Longitudinal Study

Abstract: Recent years, Finland has been one of the countries of interest in education because of its success in international comparisons. Several attempts have been made to explain what could have been behind the positive results. However, some of the challenges of Finnish education, such as the productivity (achievement/costs) or its uniformity throughout the school years have not been emphasized. Further, it is under examined in Finland, as well as worldwide, the development of the performance and the attitude durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 37 publications
2
15
0
2
Order By: Relevance
“…The shortened version is composed of three different dimensions, Liking, Self-concept and Experienced utility in a specific school subject, respectively. These three dimensions, each consisting of five items, which are strongly modified versions of the original scale, are also used in the large-scale Finnish national achievement test in lower-secondary schools by the Finnish Board of Education (Metsämuuronen, 2009;Metsämuuronen & Tuohilampi, 2014). Secondly, we used the Biohead-Citizen questionnaire (Carvalho et al, 2008;Castéra & Clément, 2014;Clément, Laurent, & Carvalho, 2007) to measure students' attitudes towards gene technology and belief in genetic determinism.…”
Section: Questionnairementioning
confidence: 99%
“…The shortened version is composed of three different dimensions, Liking, Self-concept and Experienced utility in a specific school subject, respectively. These three dimensions, each consisting of five items, which are strongly modified versions of the original scale, are also used in the large-scale Finnish national achievement test in lower-secondary schools by the Finnish Board of Education (Metsämuuronen, 2009;Metsämuuronen & Tuohilampi, 2014). Secondly, we used the Biohead-Citizen questionnaire (Carvalho et al, 2008;Castéra & Clément, 2014;Clément, Laurent, & Carvalho, 2007) to measure students' attitudes towards gene technology and belief in genetic determinism.…”
Section: Questionnairementioning
confidence: 99%
“…A Finnish longitudinal study found that pupils' attitude toward mathematics decreased over the course of comprehensive education (Metsämuuronen & Tuohilampi, 2014). This is alarming because these attitudes influence how they later respond to mathematics in their studies.…”
Section: Iscussionmentioning
confidence: 99%
“…Longitudinal research by the Finnish National Board of Education found that students' mathematical self-efficacy and enjoyment of mathematics decreased over the course of comprehensive education (Metsämuuronen & Tuohilampi, 2014). Dahlgren and Sumpter (2010) compared Swedish second and fifth graders' conceptions of mathematics and mathematics teaching via drawings with a written questionnaire.…”
Section: Introductionmentioning
confidence: 99%
“…The developmental trend of affect has been well confirmed to be declining over the school years (e.g., McLeod, 1992), especially the transition from primary to secondary school being detrimental to mathematics-related affect (e.g., Michael, Panaoura, Gagatsis, & Kalogirou, 2010). Yet, for example, Metsämuuronen and Tuohilampi's (2014) data show a decline in affect already from grade three to grade six. In this special issue, Di Martino provides evidence for the negative development taking place already over the first years of school, between grade one and grade three in all the three components of attitude they examine: vision, emotional disposition, and perceived competence.…”
Section: Development Of Affect and Achievementmentioning
confidence: 99%